Pengaruh Etos Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai (Studi Pada Pegawai Kantor Kecamatan Pakuniran Kabupaten Probolinggo) - Mohammad Yanto; N. Rachma; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT The purpose of this study was to determine the effect of the work ethic and work discipline on employee performance in Pakuniran Sub-district Office, Probolinggo Regency. This type of research used explanatory research with quantitative approaches. The sample in this study were 32 permanent employees included leaders in it. The method of analysis used in this research is hypothesis testing multiple linear regression analysis using t-test and F test. and analysis procesed with SPSS software. Data collections method used were questionnaire. From this study provides result and show that it is there partial and all at once  an relationship or work effect of work  ethic and work discipline on employee performance.Keywords : work ethic and work discipline on employee performance